Strengthening the literacy and numeracy culture among Madurese language teachers through the Pakem Maddhu community empowerment program - Moh. Hafid Effendy; Saiful Hadi; Mochamad Arifin Alatas; Isya Sayunani; Linda Safitri; Maniah (IAIN Madura, 2026)
Madurese language education faces two major challenges: declining intergenerational language transmission and limited integration of literacy and numeracy into classroom practice. A preliminary needs assessment in three partner schools in Pamekasan Regency identified low teacher competency, limited contextual teaching resources, weak student engagement, and minimal utilization of local cultural assets in learning. To address these challenges, this community engagement program adopted a Participatory Action Research (PAR) approach involving 20 Madurese language teachers, school leaders, researchers, and the Pakem Maddhu community. The program was conducted through four interactive cycles: (1) participatory problem identification and asset mapping; (2) collaborative planning and capacity building; (3) classroom implementation with mentoring and observation; and (4) reflective evaluation to improve teaching practices and learning resources. Local cultural assets, including paribasan, pantun, tembang macapat, and Madurese batik motifs, were integrated into literacy- and numeracy-based learning activities. Program evaluation, using competency tests, questionnaires, classroom observations, and reflective discussions, demonstrated substantial improvements in teacher competency (52.0 to 78.3; p < .001), increased teacher confidence in using digital learning media (85%), and higher student interest in Madurese language learning (38.6% to 72.4%; p = .004). Beyond improving instructional competence, the program strengthened collaboration among teachers, schools, and the local community, resulting in contextual teaching modules, lesson plans, digital learning resources, and a sustainable professional learning network. The program contributes a replicable, community-based empowerment model that integrates Participatory Action Research, local cultural assets, literacy and numeracy integration, and teacher professional development for regional language education.